Mapping of atomic catalyst on graphdiyne. (August 2019) - Sun, Mingzi; Wu, Tong; Xue, Yurui; Dougherty, Alan William; Huang, Bolong; Li, Yuliang; Yan, Chun-Hua
Abstract: Atomic catalysts (AC) as the frontier in atomic catalyst have attracted tremendous attention in recent electrocatalyst research. The performance of ACs strongly depends on the electronic interaction between the atoms and support. To supply a direct strategy for discovering more promising electrocatalysts, we propose a comprehensive mapping study of anchoring transition metals on the graphdiyne (GDY). The electron transfer ability and zero-valence stability are quantified based on the redox process between surface metal and GDY support. The different electron transfer number and directions between the transition metals and GDY are also compared, in which the initial one-electron transfer is the most difficult. Among all the TMs, Co, Pd and Pt have displayed the exceptional stability of zero-valence catalyst based on the evident energy barrier difference between losing electrons and gaining electrons. Experimental results support the remarkable performance of our screened candidates, which have opened a new possibility to achieve novel high-performance zero-valence ACs. Moreover, we outlook the introduction of the deep-learning algorithm in the future advanced mapping strategy for achieving more complicated ACs. This work not only supplies innovative electrocatalyst candidates but also exhibits an innovative approach for studying the electrocatalysts that can further apply to more material systems. Graphical abstract: Illustration of the mapping strategy for screening AC candidates.Image 1 Highlights: A practical mapping strategy has been proposed to screen possible zero-valence atomic catalyst for anchoring graphdiyne. The electrocatalytic properties of transition metals on graphdiyne are comprehensively studied and compared. Pt, Co, Pd are screened out to achieve highly efficient zero valence atomic catalysts.